2013
DOI: 10.3748/wjg.v19.i15.2355
|View full text |Cite
|
Sign up to set email alerts
|

Patient comfort and quality in colonoscopy

Abstract: The best colonoscopists have a higher CIR, use less sedation, cause less discomfort and find more polyps. Measuring patient comfort is valuable in monitoring performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 31 publications
0
46
1
Order By: Relevance
“…Comfort levels are affected by many factors including technique and some evidence suggests that endoscopists performing better on other KPI also provide a more comfortable patient experience with less sedation 190. A national audit10 demonstrated that moderate or severe discomfort was experienced by approximately 10% of 20 000 cases recorded.…”
Section: The Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comfort levels are affected by many factors including technique and some evidence suggests that endoscopists performing better on other KPI also provide a more comfortable patient experience with less sedation 190. A national audit10 demonstrated that moderate or severe discomfort was experienced by approximately 10% of 20 000 cases recorded.…”
Section: The Standardsmentioning
confidence: 99%
“…Several systems for scoring patient comfort exist, such as the Gloucester nurse-reported 5-point scale,190 which combines features of pain, frequency of pain and distress. Patient-reported comfort scores use either 4-point Likert scales or 100 mm visual analogue scales in lightly or unsedated patients 191.…”
Section: The Standardsmentioning
confidence: 99%
“…[10] Comfort during colonoscopy was reported by the nurse-assessed modified GCS. [23] Achieving an adequate PICI was defined as a procedure with cecal intubation, delivery of a maximum dose of 2.5 mg midazolam and Gloucester Comfort Scale (GCS) between 1 and 3 (no to mild discomfort) . We adjusted the maximum dose of 2 mg midazolam (used by Valori et al) [8] to 2.5 mg for practical reasons.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Education and training are key for quality and patient safety. Serious issues regarding gastrointestinal endoscopy quality have been demonstrated in several studies, mainly related to missed lesions, adverse events (AEs), and poor patient experiences [1,2]. To improve the quality of endoscopy procedures, the European Society of Gastrointestinal Endoscopy (ESGE) has during the last decade developed recommendations for quality targets and quality performance indicators (KPI) [3].…”
mentioning
confidence: 99%